Pengorganisasian dalam Pendidikan Islam: Struktur Organisasi, Pembagian Tugas, dan Koordinasi dalam Lembaga Pendidikan Islam - Anisatul Luthfia; Sunarto Sunarto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Organization is one thing that cannot be separated from the scope of Islamic Education. This study aims to identify the organization in Islamic education plays a very important role in creating an efficient and effective system to achieve the desired educational goals. This study uses a qualitative method with a literature study approach, where data is obtained through documentation sourced from scientific journals and relevant books that discuss the organization and management of Islamic education. To analyze the data, content analysis techniques are used. The results of the study indicate that organization in Islamic education has a very important role in achieving better educational goals. A clear organizational structure, proper division of tasks, and good coordination between elements in educational institutions can increase the effectiveness and efficiency of the educational process in Islamic educational institutions.